Studi Modernisasi Nelayan di Kota Kendari (Studi Kasus Armada Purse Seine di Pelabuhan Perikanan Samudera Kendari) - Fitriany, Dian; Hamzah, Awaluddin; Wianti, Nur Isiyana (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This study aims to determine the process of transformation of fishermen to succeed in fisheries modernization, Knowing Factors that play a role in the success of modernization of fishermen. This research was conducted in January 2018 until March 2018 at Fishery Port of Samudera Kendari. Determination of key informants in this study amounted to 4 people, where there is One owner of the ship, two skippers of the ship who is the second owner and leader of the boat, and a captain who is the leader of the ship. Determination of key informants is intended because they are the key to know the process of modernization of fishery business from the beginning of its development until now. This research uses descriptive qualitative analysis method. The results of this study indicate that the elite of Indigenous entrepreneurs is a pioneer elite born in the first modernization period from 1970 to 1980. His business started from traditional fishermen engaged in fish auction business became the head of the fishermen group so that they can access the fishery assistance to develop the business in PPS Kendari. While the Chinese entrepreneurs elite is a followers elite born after the third period of modernization that is after 1990 the business started from employees at the company Cilacap. Because of the potential in him and is the ethnic Chinese he then get help from the company Cilacap owned by the company Cilacap. Factors that play a role in the success of modernization of fishermen can be seen from the elite success of Indigenous businessmen and elite of Chinese businessmen. Where the elite of Native entrepreneurs in fishery modernization there are factors that play a role is the business experience that is as a traditional fisherman and work in fish auctions and then transformed into fisherman owners who have their own company with a fleet of ships that many. While Chinese businessmen are more to ethnic background factors so as to get capital assistance from large Chinese ethnic companies. Furthermore, the elite of indigenous entrepreneurs is supported by the government through the help of the fishing fleet, while the Chinese business elite is supported by the Chinese pioneering elite of Cilacap.